2021-05-20 Maintenance illustration by-David-Revoy - David Revoy (Wikimedia Commons, 2021)
Notice iconographique issue de Wikimedia Commons. Titre: 2021-05-20 Maintenance illustration by-David-Revoy. Maintenance illustration by David Revoy
Droits : Licence Creative Commons Attribution 4.0 via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie